Da Íris ao Hongolo: o movimento LGBTQIA+ angolano no século XXI - Ferreira, Tiago (Latitude, 2024)
The present work seeks to map (through interviews with activists from the Angolan Identity Archive and Associação Íris – two of the main LGBTQIA+ organizations in Angola) three key moments in the history of the LGBTQIA+ movement in the country. The first moment takes place between 2002 and 2016, when the first Angolan LGBTQIA+ organization was created from the fight against HIV. The second moment is the moment when the new penal code was discussed and approved. The third moment deals with the future of the LGBTQIA+ movement in Angola and its relationship with colonialism. We spoke with three Angolan activists in order to describe each of these historical phases, seeking to use their life experiences as analytical tools for understanding the history of the LGBTQIA+ movement in Angola. Finally, we test the thesis that Angola does not have an stablished civil society.